Morpho-biochemical Identification and Antimicrobial Susceptibility Testing of Bacterial Isolates from Chicken Eggs in District Faisalabad - Neelma Ashraf; Abid Rashid; Anam Rasool; Muhammad Mudassar Ashraf; Ahsan Sarwar; Muhammad Ahsan Naeem (International Journal of Antibiotic Research, 2018)
Microorganisms are the main cause of food-borne illness in humans that may occur by consuming unhygienic products from poultry and other sources. With the passage of time bacterial resistance to antibiotics is ever-increasing which necessitates development of new antibiotics. One of the most obvious reasons of antimicrobial resistance in human-beings is the consumption of contaminated food with microbes. The aim of present study is to isolate, identify and characterize the food-borne pathogens from chicken eggs. For this purpose, a total of 240 egg samples were collected from eight different towns of Faisalabad. Samples were collected from egg surface, yolk, albumin and egg tray. Isolation, identification and characterization of commonly occurring egg borne pathogens including E. coli, Salmonella spp., Bacillus subtilis, Staphylococcus aureus were carried out by different cultural, morphological and biochemical tests. Antibiotic resistance pattern of recovered bacterial pathogens was determined by disk diffusion method (Kirby-Bauer). Zone of inhibition was measured through vernier calliper. The results revealed a high prevalence of Salmonella entitidis with 40.83% following Staphylococcus aureus with 22.08%, Escherichia coli with 17.92% and Bacillus subtilis in a lower ratio with 2.5%. The antibiotic sensitivity test showed different resistance patterns of the isolated microbes. For this purpose, five different drugs were used that included cefotaxime, tetracycline, gentamicin, levofloxacin and penicillin. Bacillus subtilis was highly resistant to penicillin and cefotaxime. Whereas, E. coli showed resistance to three antibiotics that were tetracycline, cefotaxime and penicillin. The only drug to which Staphylococcus aureus showed resistance was cefotaxime. Salmonella was resistant to tetracycline and gentamicin. The study concluded that chicken egg is contaminated with a number of bacteria that could be pathogenic or not. So, there is need of proper attention to cope up with possible future egg-borne illnesses.
Keywords: Biochemical